Adolescent Weapon Carrying Inside and Outside of School: The Impact of Experiences and Perceptions of Violence - McCuddy, Timothy (American journal of criminal justice, 2024)
This study examined factors that distinguish adolescent weapon carrying in school compared to only in the community. We look at how experiences (offending, victimization, and gang-involvement) and perceptions (school, neighborhood, individual) toward violence are associated with self-reported weapon carrying in these two locations. Data came from two waves of the University of Missouri – St. Louis Comprehensive School Safety Initiative, a longitudinal study on the causes and consequences of school violence. Multinomial logistic regression was used to predict weapon carrying among three mutually exclusive categories: those who do not carry, those who carry only in the community, and those who carry both in school and in the community. We find that victim/offenders are more likely to carry weapons regardless of context, but school weapon carrying is positively associated with fatalism and gang-involvement. One school factor, school commitment, impacted carrying both inside and outside of school. Our results identify unique factors that can reduce adolescent weapon carrying in general and specifically in school.